Office Automation and Secretarial Productivity in Rivers State University (American International Journal of Nursing Education and Practice, 2020)
This study investigated Office Automation and Secretarial Productivity in Rivers State. The objective was to examine the extent to which office automation affects the productivity of secretaries. Forty-five secretaries were selected from thirty-eight departments and seven faculties in the Rivers State University. The study adopted four research questions and four null hypotheses. Copies of the Questionnaire were administered to the secretaries. Mean and Standard Deviation were used to analyze the research questions while Pearson Product Moment Coefficient was used to test the hypotheses. Findings revealed that office automation equipment has positive and significant effects on the productivity of secretaries in the university. From the correlation coefficient, the study concluded that office automation affects productivity to a great extent. It, therefore, recommended that the office environment should be redefined to fit modern office technologies for effective secretarial functions, and there should be policies in the organization for secretarial training for better performance of the secretaries in the university. Secretaries should not entertain fear that automated devices will displace them but rather see it as something which has come to assist them to do their jobs in order to improve their efficiency and productivity.